Diagnostic value of miRNA expression and right ventricular echocardiographic functional parameters for chronic thromboembolic pulmonary hypertension with right ventricular dysfunction and injury - Ran Miao; Juanni Gong; Xiaojuan Guo; Dichen Guo; Xinyuan Zhang; Huimin Hu; Jiuchang Zhong; Yuanhua Yang; Yidan Li (BMC Pulmonary Medicine, 2022)
Abstract Background We aimed to establish the relationships between the expression of microRNAs (miRNAs) and echocardiographic right ventricular (RV) function parameters, and to explore the effectiveness and clinical value of miRNA expression in predicting RV injury and dysfunction in patients with chronic thromboembolic pulmonary hypertension (CTEPH). Methods In this retrospective study, clinical data were collected from eight CTEPH patients and eight healthy individuals. RV parameters on echocardiography were analyzed, and the expression levels of specific miRNAs were measured by quantitative real-time PCR. Correlation analysis was performed on structural and functional RV parameters and five candidate miRNAs (miR-20a-5p, miR-17-5p, miR-93-5p, miR-3202 and miR-665). The diagnostic value of RV functional parameters and miRNAs expression was assessed by receiver operating characteristic (ROC) curve analysis and C statistic. Results Among the tested miRNAs, miR-20a-5p expression showed the best correlation with echocardiographic RV functional parameters (P < 0.05), although the expression levels of miR-93-5p, miR-17-5p and miR-3202 showed positive associations with some RV parameters. ROC curve analysis demonstrated the ability of miR-20a-5p expression to predict RV dysfunction, with a maximum area under the curve of 0.952 (P = 0.003) when the predicted RV longitudinal strain was less than –20%. The C index for RV dysfunction prediction by the combination of miRNAs (miR-20a-5p, miR-93-5p and miR-17-5p) was 1.0, which was significantly larger than the values for miR-93-5p and miR-17-5p individually (P = 0.0337 and 0.0453, respectively). Conclusion Among the tested miRNAs, miR -20a-5p, miR -93-5p and miR -17-5p have potential value in the diagnosis of CTEPH based on the correlation between the abnormal expression of these miRNAs and echocardiographic parameters in CTEPH patients. miR-20a-5p showed the strongest correlation with echocardiographic RV functional parameters. Moreover, expression of a combination of miRNAs seemed to show excellent predictive power for RV dysfunction.